Transcriptome analysis reveals the molecular mechanism of γ-linolenic acid eradicating the biofilm of vancomycin-resistant Enterococcus faecium - Wei, Ming; Wang, Peng; Li, Tianmeng; Liu, Jun; Wang, Yu; Gu, Li; Wang, Shuai (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionVancomycin-resistant Enterococcus faecium (VRE-fm) biofilms pose a significant clinical challenge due to the limited effectiveness of traditional antibiotics. This study investigates the potential of γ-linolenic acid (GLA) as a novel antibiofilm agent.MethodsTranscriptome analysis was performed on the V27 isolate, comparing cells in mature biofilms treated with and without GLA. The findings were further validated using qRT-PCR on six VRE-fm isolates and two E. faecalis isolates.ResultsTranscriptome analysis revealed a significant downregulation in the expression levels of genes associated with biofilm formation, including fruA, fruB, sgrA, lpxtg-cwa, tfpp, lafA, lafB, malP, fsrA, and fsrC’, while a significant upregulation was observed in the expression of fsrBD. Validation by qRT-PCR in six VRE-fm isolates confirmed the significant changes in the expression levels of all genes except for lpxtg-cwa, with statistical significance. The expression of bgsB and bgsA genes, which are the homologs of lafA and lafB genes, along with the Fsr-regulated genes gelE and sprE in E. faecalis, were also found to be downregulated by GLA. In addition, KEGG analysis identified specific metabolic pathways that were significantly downregulated by GLA.ConclusionGLA effectively targets multiple aspects of biofilm formation in VRE-fm, including the downregulation of key biofilm-related genes, the inhibition of quorum sensing systems, and the modulation of metabolic pathways. GLA emerges as a promising candidate for eradicating Enterococcus biofilms.